Surface modified malaysian Ceiba Pentandra (L.) Gaertn. as natural oil adsorbent: article - Mat Noh, Ahmad Zakwan; Megat Khamaruddin, Putri Nadzrul Faizura (2018)
The risk of oil spills escalate as the petroleum industry growing and the toxic hydrocarbons released to the environment are harmful to both animals and living things. Producing a cost-efficient and environmental-friendly sorbent are fundamentals. Sorbent must not leave traces of harmful chemicals which may later on affect the nature. Adsorption technique by using kapok fiber has been proven to be the most promising method compared to the other oil-containment approaches. Kapok have an excellent hydrophobic-oleophilic structure. In this study, four-hour esterification of fatty acids (oleic acid and decanoic acid) at 50˚C±5˚C will modify the surface characteristics of the kapok fiber in order to identify the effects on the oil sorption and dynamic oil retention capacity. The oil treatment protocol follows the standard F72699 (ASTM, 1998c). This research focuses on analyzing the sorption capacity of raw kapok and its modified versions in accordance to the varied oil viscosity (diesel, engine oil, and light crude oil). In addition, the experimental results are compared with adsorption isotherms models which are Langmuir and Freundlich to identify the sorption behavior of the adsorbent. The functional groups of kapok can be retrieved from performing Fourier-Transform Infrared (FTIR). Raw, oleic grafted, and decanoic grafted kapok show high sorption intake for crude oil; 66.50g/g, 73.22g/g, and 79.27g/g respectively. Raw kapok shows highest sorption for diesel (50.41g/g) and engine oil (60.32g/g). However, the modified versions of kapok show better dynamic retention capacity compared to the raw kapok. Malaysian kapok behaves similarly as the Langmuir isotherm model.